Clearance of stored red blood cells is not increased compared with fresh red blood cells in a human endotoxemia model. Issue 6 (4th April 2016) - Peters, Anna L.; Beuger, Boukje; Mock, Donald M.; Widness, John A.; de Korte, Dirk; Juffermans, Nicole P.; Vlaar, Alexander P.J.; van Bruggen, Robin
Abstract : BACKGROUND: It is thought that the clearance of transfused red blood cells (RBCs) is related both to the storage time of the transfusion product and to the inflammatory status of the recipient. We investigated these effects in a randomized, "two‐hit, " healthy volunteer transfusion model, comparing autologous RBCs that were stored for 35 days with those that were stored for 2 days. STUDY DESIGN AND METHODS: Healthy male volunteers donated 1 unit of autologous RBCs either 2 days (2D) or 35 days (35D) before the study date. The experiment was started by infusion of 2 ng/kg lipopolysaccharide ("first hit"). Two hours later, the stored RBCs ("second hit") were reinfused, followed by the labeling of RBCs with biotin. Clearance of biotin‐labeled RBCs (BioRBCs) was measured during the 5‐hour posttransfusion endotoxemia period along with measurements of phosphatidylserine (PS) exposure, lactadherin binding, and expression of CD47 (cluster of differentiation 47; a transmembrane protein encoded by the CD47 gene). RESULTS: In the 2D stored RBCs group, 1.5% ± 3.4% of infused BioRBCs were cleared from the circulation 5 hours posttransfusion versus 4.8% ± 4.0% in the 35D stored RBCs group (p = 0.1). There were no differences in PS exposure, lactadherin binding, or CD47 expression between fresh and stored RBCs or between pretransfusion and posttransfusion measurements. CONCLUSION: Our study shows a low clearance of RBCs even during endotoxemia. Furthermore, short‐term clearance of BioRBCs during endotoxemia was not related to storage duration. Consistent with these observations, PS exposure, lactadherin binding, and CD47 expression did not differ between 2D and 35D stored cells before or after transfusion. We conclude that, in the presence of endotoxemia, clearance of 35D stored autologous RBCs is not increased compared with 2D stored fresh RBCs.